Ana María Cano González: Llingua, tierra, nomes… Estudios d’Onomástica Románica (1987-2017) - García Gallarín, Consuelo (Lletres Asturianes, 2022)
Ana María Cano González: Llingua, tierra, nomes… Estudios d’Onomástica Románica (1987-2017)